THE EFFECT OF ONION (ALLIUM CEPA L.) ON HAIR HEALTH: BIOACTIVE PROPERTIES AND PRACTICAL APPLICATIONS - Boltaeva Khurshida Odilovna (Modern American Journals, 2025)
Onion (Allium cepa L.) is a widely cultivated and consumed vegetable known for its culinary and medicinal properties. Recently, its role in hair health has gained scientific and cosmetic interest due to its rich phytochemical composition, particularly sulfur-containing compounds, flavonoids, and antioxidants. This paper reviews the bioactive compounds in onion relevant to hair growth, explores its potential mechanisms of action, evaluates clinical and preclinical studies, and discusses practical applications including topical formulations. The evidence suggests that onion juice can stimulate hair regrowth, reduce hair thinning, and improve scalp health, offering a natural and accessible alternative to synthetic hair care products.